Propuesta de implementación de un sistema de gestión de calidad en la fase preanalítica del Laboratorio Clínico “SER”, basado en la norma ISO 9001:2015 - González Cabrera, Aly Yamaela (2023)
A Quality Management System (QMS) nowadays, is a strategy to promote competition in organizations, where coordinated processes are done and set, with the main goal of satisfying the users' necessities. The present research work has established as a primary goal “Create a Quality Management System Proposal in the preanalytical stage at the Clinical Laboratory “SER”, based on Norma ISO 900:2015”. To accomplish the set goals, a previous study of quantity, descriptive, and exploring type was done; in the first phase the diagnosis of the real situation based on the preanalytical phase applying a Check List or a verification list based on Norma ISO 9001:2015; where a percentage of 49.09% was the evidence of accomplishment, the 28.18% was partial accomplishment and a 22.73% of non-complementation. In the second stage paperwork evidence was designed and required for a proposal of QMS, between the documents done you can find protocols, instructions, procedures, and manuals. Finally, in the third stage, the documental existent evidence was updated, based on Norma ISIO 9001:2015 lines. This proposal for the implementation of QMS allowed to improve the productivity, efficiency, and effectiveness in each phase, giving and adding value to the service, which increases the level of user satisfaction